a-synuclein PET Imaging: From Clinical Utility in Multiple System Atrophy to the Possible Diagnosis of Parkinson’s Disease - Francesca Capotosti (Cells)
The development of PET tracers for the detection of pathological alpha-synuclein (a-synuclein) has the potential to revolutionize the diagnosis, monitoring, and therapeutic interventions of synucleinopathies, including Parkinson’s disease. The journey toward identifying effective PET imaging agents, however, has faced significant challenges due to the complexity and heterogeneity of the a-synuclein structures. Achieving the goal is further compounded by the low density of the pathological target, necessitating that the tracer exhibits a high binding potential, as well as the co-existence of other protein aggregates, requiring the tracer to be highly specific and selective for a-synuclein. In this perspective article, the challenges regarding developing PET tracers for a-synuclein are explored and summarized, together with the most significant recent advances in the field. These include the approaches used by our laboratories, leading to the publication of the first clinical PET images of a-synuclein pathology in patients with multiple system atrophy (MSA). Building on the current understanding of the different a-synuclein species and findings based on the success of PET tracers in the field of neurodegenerative diseases, future directions are considered also to achieve the imaging of a-synuclein pathology in Parkinson’s patients.